2006
DOI: 10.1016/j.clpt.2006.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in CYP3A activity using intravenous and oral midazolam

Abstract: Although women showed significantly greater hepatic and intestinal CYP3A activity, only a minor sex difference in AUC was noted. Therefore the observed disparity may be of negligible clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 40 publications
5
53
0
Order By: Relevance
“…CV% for men remained constant at 28% from baseline to ketoconazole inhibition, whereas CV% increased from 28 to 51% for females. Whether this observation is unique to our subjects or a sex difference in CYP3A activity is unknown; however, our previous data have suggested that women show modestly greater CYP3A isozyme activity compared with men when using oral midazolam as a probe (Chen et al, 2006). Monte Carlo simulations were performed to determine the distribution of exposure using a 10,000-subject simulation.…”
Section: Discussionmentioning
confidence: 96%
“…CV% for men remained constant at 28% from baseline to ketoconazole inhibition, whereas CV% increased from 28 to 51% for females. Whether this observation is unique to our subjects or a sex difference in CYP3A activity is unknown; however, our previous data have suggested that women show modestly greater CYP3A isozyme activity compared with men when using oral midazolam as a probe (Chen et al, 2006). Monte Carlo simulations were performed to determine the distribution of exposure using a 10,000-subject simulation.…”
Section: Discussionmentioning
confidence: 96%
“…Although there are some conflicting results, the majority of studies suggest that women exhibit 20-50% faster clearance of CYP3A-metabolized drugs. Those drugs include triazolam, diazepam, midazolam, methylprednisolone, nifedipine, diltiazem, verapamil, ifosfamide, cyclosporine, erythromycin, tirilazad, quinine and alprazolam; 1,4,29) however, the observed sex differences of certain substrates are dependent on the administration route. For example, clearance of intravenously administrated verapamil is greater in Model 1: higher expression of CYP3A4 enzyme in women causes the sex difference.…”
Section: Sex Difference Of Cyp3a4mentioning
confidence: 99%
“…For example, mean MDZ clearances were greater in women in several investigations, reaching statistical significance in some (Greenblatt et al, 1984;Gorski et al, 1998Gorski et al, , 1999Zhu et al, 2003;Chen et al, 2006c;Chung et al, 2006;Kharasch et al, 2007;Hu et al, 2009), whereas other studies found equivalence (Kashuba et al, 1998;Dresser et al, 2003;Floyd et al, 2003;Gorski et al, 2003;Eap et al, 2004;Chen et al, 2006a) or even insignificantly higher clearances in men (Thummel et al, 1996). Results of the largest-scale investigation (41 women and 58 men) showed that systemic clearances were 30% greater in women, but there was no sex difference for oral MDZ (Kharasch et al, 2007).There were two retrospective studies on this topic, and both studies showed significant sex-dependent differences (Chen et al, 2006b;Miao et al, 2009). Miao et al (2009) concluded that women exhibited 19% higher weight-corrected systemic clearance and 38% higher oral clearance than men (P Ͻ 0.05).…”
mentioning
confidence: 98%
“…Studies conducted on elderly volunteers were included because there was no significant difference in CYP3A activity between young and old populations (Klotz, 2009). According to the retrospective studies by Miao et al (2009) and Chen et al (2006b), the sex difference in MDZ clearance ranged from 11 to 38%. Many relevant studies on this topic used a small sample size.…”
mentioning
confidence: 99%
See 1 more Smart Citation